Catastrophic antiphospholipid syndrome causing ST-segment elevation myocardial infarction with non-obstructive coronary arteries. Issue 1 (10th January 2019) - Cranley, James; Krishnan, Unni; Tweed, Katharine; Duehmke, Rudolf Martin
Abstract : A 51-year-old woman with known primary antiphospholipid syndrome presented with a 4-day history of chest and abdominal pain, inferior ST-segment elevation on a 12-lead ECG and a subtherapeutic international normalised ratio. In view of a significantly raised high-sensitivity troponin I assay, inferior wall hypokinesis on transthoracic echocardiography and despite unobstructed epicardial vessels on emergency coronary angiography, a diagnosis of myocardial infarction was made. Furthermore, the patient also developed both bilateral adrenal haemorrhages leading to acute adrenal insufficiency and microvascular thrombotic renal disease concurrently. The patient therefore fulfilled the diagnostic criteria for catastrophic antiphospholipid syndrome presenting with cardiac, endocrine and renal involvement. Early diagnosis permitted appropriate treatment with anticoagulation, dual antiplatelet therapy, secondary prevention and corticosteroid replacement therapy and led to a full recovery. This case highlights first the importance of adequate anticoagulation in antiphospholipid syndrome and, second, the potentially fatal, multiorgan complication of failure to do so.